The significant immune escape of pseudotyped SARS-CoV-2 variant Omicron - Zhang, Li; Li, Qianqian; Liang, Ziteng; Li, Tao; Liu, Shuo; Cui, Qianqian; Nie, Jianhui; Wu, Qian; Qu, Xiaowang; Huang, Weijin; Wang, Youchun (Emerging microbes & infections, 2022)
The emergence of Omicron/BA.1 has brought new challenges to fight against SARS-CoV-2. A large number of mutations in the Spike protein suggest that its susceptibility to immune protection elicited by the existing COVID-19 infection and vaccines may be altered. In this study, we constructed the pseudotyped SARS-CoV-2 variant Omicron. The sensitivity of 28 serum samples from COVID-19 convalescent patients infected with SARS-CoV-2 original strain was tested against pseudotyped Omicron as well as the other variants of concern (VOCs, Alpha, Beta, Gamma, Delta) and variants of interest (VOIs, Lambda, Mu). Our results indicated that the mean neutralization ED50 of these sera against Omicron decreased to 66, which is about 8.4-folds compared to the D614G reference strain (ED50 = 556), whereas the neutralization activity of other VOC and VOI pseudotyped viruses decreased only about 1.2-4.5-folds. The finding from our in vitro assay suggest that Omicron variant may lead to more significant escape from immune protection elicited by previous SARS-CoV-2 infection and perhaps even by existing COVID-19 vaccines.